RESPON TANAMAN TERUNG TERHADAP PEMBERIAN AMELIORAN PADA TANAH GAMBUT - Darussalam; Elly Mustamir (AGROISTA : Jurnal Agroteknologi, 2019)
Eggplant is one of holticulture most widely used as edible fruit and also as vegetable. Furthermore, eggplants have delicious taste, the price per kg is relatively cheap and high levels of nutrition such as protein, carbohydrate, and vitamins. The aims of the research were to determine the effect of residue of 5 ameliorants on growth and yield of eggplant growth on peat soil. The five residu of ameliorants used as lime of dolomites, ash of coconute fibre, ash of bivalve shell, ash of empty bunch of palm oil and ash of sawmill waste. Design of experimental was used Random Complate Block Design with 5 treatments and 5 replication per block and 3 eggplant as samples. Parameters of research were leaves areas (cm2), root volume (ml), shoot dry weight (g), number of fruits per eggplant (fruits), weight of fruits per eggplant (g), length of fruits per eggplant (cm), fruit diameter per eggplant (cm). The result indicated that residue of dolomites (7,99 tons/ha equal to 2,5 kg/ block), showed that the residue effect were the lowest and residue ash of sawmill waste indicate the best effect on character of leaves area, weight of fruits, fruits diameter and number of fruits per eggplant. Keyword: eggplant, peat soil, ameliorant, residue